Evaluation of system resilience : a numerical approach - Chan, Guo Jun (2018)
Scale-free network are very apparent in our daily lives. The Internet and many other networks are closely related to scale-free network. Scale-free network modelling can be very useful to simulate real life networks. Due to this similarity, simulation of scale-free network can translate to real life results. Predictive model behavior and even theories can be put to the test through scale-free network simulation. In this paper, we will explore the construction of a scale-free network using Matlab and the robustness of a scale-free network. Robustness of a scale-free network will be tested with intentional attacks and random attacks. Improvements to the resilience of a scale-free network are also implemented. Random repair and random 2-hop repair methods are attempts to improve the robustness of the network under attack.